Evaluating Primary Care Providers' Views on Survivorship Care Plans Generated by an Electronic Health Record System - Donohue, SarahMaria (J Oncol Pract, 2015)
PURPOSE: Survivorship care plans for cancer survivors may facilitate provider-to-provider communication. Primary care provider (PCP) perspectives on care plan provision and use are limited, especially when care plans are generated by an electronic health record (EHR) system. We sought to examine PCPs' perspectives regarding EHR-generated care plans. METHODS: PCPs (N = 160) who were members of the Wisconsin Research and Education Network listserv received a sample 10-page plan (WREN cohort). PCPs (n = 81) who had or were currently seeing survivors enrolled onto one of our survivorship clinical trials received a copy of the survivor's personalized care plan (University of Wisconsin [UW] cohort). Both cohorts received a survey after reviewing the plan. All plans were generated within an EHR. RESULTS: Forty-six and 26 PCPs participated in the WREN and UW cohorts, respectively. PCPs regarded EHR-generated plans as useful in coordinating care (88%), understanding treatments (94%), understanding treatment adverse effects (89%), and supporting clinical decisions (82%). Few felt using EHR-generated plans would disrupt clinic workflow (14%) or take too much time (11%). Most (89%) preferred receiving the plan via EHR. PCPs reported consistent provision (81%) and standard location in the medical record (89%) as key factors facilitating their use of survivorship care plans. Important facilitators of care plan use included a more abbreviated plan, ideally one to three pages (32%), and/or a plan specifically tailored to PCP use (57%). CONCLUSION: Plans were viewed as useful for coordinating care and making clinical decisions. However, PCPs desired shorter, clinician-oriented plans, accessible within an EHR and delivered and located in a standardized manner.